2022
DOI: 10.3390/cancers14092252
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Importance of ctDNA in Rectal Cancer: A Critical Reappraisal

Abstract: The treatment of locally advanced rectal cancer (LARC) has evolved during the last decades, but recurrence remains a problem. Circulating tumor DNA (ctDNA) may result in an individualized treatment approach with improved survival and quality of life, but diverging results impede further development. In this systematic review, we addressed the quality of reporting and its impact on the interpretation of ctDNA results. We performed a systematic literature search using subject headings and search terms related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Eight of the nine studies showed some degree of correlation between ctDNA and either response to chemoradiation, risk of recurrence or disease-free survival. A second systematic review also included nine studies and investigated the association between clinical outcomes and ctDNA at different time points (at diagnosis, after chemoradiation, and after surgery) ( 38 ). No association was found between treatment response and ctDNA status at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Eight of the nine studies showed some degree of correlation between ctDNA and either response to chemoradiation, risk of recurrence or disease-free survival. A second systematic review also included nine studies and investigated the association between clinical outcomes and ctDNA at different time points (at diagnosis, after chemoradiation, and after surgery) ( 38 ). No association was found between treatment response and ctDNA status at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Response to anti-cancer treatment is a multifactorial process that is not only dependent on tumor size and morphology, but also on other patient-factors and aspects of tumor biology that we cannot hope to capture by imaging. Important next steps in research will therefore be to combine image-based prediction methods with other clinical, histopathological, immunohistochemical and genetic biomarkers that have shown promise as predictors of response and that were unfortunately not available for analysis in this current retrospective study cohort [ 27 , 29 33 ]. Only this way can we hope to achieve a strong enough predictive performance to serve as a basis for clinical decision-making, aiming to further boost personalized therapy in rectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 21 publications including 1499 patients 100 demonstrated that ctDNA could be used to predict pCR, whereas 3 other reviews suggested that it could not. [101][102][103] At this time, there is not enough high-level evidence to support using ctDNA to predict pathologic response.…”
Section: A Watch-and-wait Strategy Can Be Offered To Selected Patient...mentioning
confidence: 99%